Abdominal aortic aneurysmectomy in renal transplant recipients - Gil, Roberto Jiménez; Gimeno, Francisco Morant (Archives of Medical Science, 2009)
An increasing number of patients with kidney transplants are found to develop abdominal aortic aneurysm (AAA) in the post-transplant period. Aortic surgery in these patients places the pelvic allograft at risk for ischaemic damage. We report successful repair of two AAA in renal transplant recipients using cold graft perfusion and local hypothermia to protect the renal allograft during aortic cross-clamping. Conventional AAA surgery in patients with a kidney transplant is feasible without impairing renal function. In situ cold perfusion represents a safe method of renal protection with low risk of atheromatous embolization. Likewise, endovascular techniques may be an option in selected cases